Typification of thirty six names of thirty five recognized taxa in Impatiens (Balsaminaceae), endemic to Western Ghats - Singh, Rajeev Kumar (Phytotaxa, 2016)
The genus Impatiens Linnaeus (1753: 937) consists of about 1000 species, distributed in the tropical and subtropical regions of the Old World as well as in the northern temperate regions (Mabberley 2008). In India there are about 215 species of Impatiens recorded so far, of which 142 species are endemic, and the diversity occurs in two regions, viz. the Eastern Himalayas and the Western Ghats. During systematic study of this genus in the Western Ghats region of India, I realized that it was necessary to typify 36 binomials of 35 recognized endemic species from the Western Ghats, because no specific herbarium sheet was cited as holotype in protologue of these names and also yet not typified (Vivekananthan et al. 1997, Rathakrishnan 2005, Bhaskar 2012). Here lectotypes are chosen for 35 names and a neotype for one name. The images of the lectotypes, isolectotypes, residual syntypes and neotype specimens at BR, E, G, K, M, MPU, NY and P are available online (http://www.br.fgov.be/research/collections/herbarium, http://elmer.rbge.org.uk/bgbase/vherb/bgbasevherb.php, http://www.ville-ge.ch/musinfo/bd/cjb/chg, http://apps.kew.org/herbcat/navigator.do, https://plants.jstor.org, http://www.collections.univ-montp2.fr/herbier-mpu-presentation/base-de-donnees-botanique-herbier-mpu, http://sweetgum.nybg.org/science/vh & https://science.mnhn.fr/institution/mnhn/search/form), while those at BSI, CAL and MH are not available online. Therefore, the images of selected lectotypes from MH are provided here.